Transpressive inversion of a Mesozoic extensional forced fold system with an intermediate décollement level in the Basque‐Cantabrian Basin (Spain). Issue 2 (26th April 2013) - Tavani, Stefano; Carola, Eloi; Granado, Pablo; Quintà, Anna; Muñoz, Josep Anton
Abstract [1] In the Basque‐Cantabrian Basin (Spain), normal faulting and associated folding occurred during Late Jurassic to Early Cretaceous rifting. Cenozoic Pyrenean thick‐skinned transpressive inversion in the western parts of the basin preserved the first‐order extensional architecture. Integration of geological maps and seismic profiles has permitted to fully constrain the style of extensional deformation and subsequent inversion in the western portion of the Basque‐Cantabrian Basin. Extensional faults offset the Paleozoic basement up to Lower Triassic rocks. The presence of an efficient décollement level represented by Triassic evaporites produced the decoupling between basement rocks and the Upper Triassic to Middle Jurassic prerift cover sequence. Extensional forced folding occurred in the cover, driven by basement faulting and the migration of evaporites toward the hanging wall of the extensional faults, with salt welds developing away from them. Upper Jurassic to Lower Cretaceous syn‐rift sediments deposited synchronously with forced folding, which led to the development of extensional growth geometries associated with both master faults and nearly‐transverse faults. Syn‐rift growth sequences are characterized by downlap and onlap relationships with the underlying prerift units, interpreted as the result of along‐strike variations of master fault extensional displacement rate. Cenozoic Pyrenean contraction generated the right‐lateral transpressive inversion of basement master faults and the almost dip‐slip reactivation of transverse extensional faults.